Factors Determine Marketing Research Utilization Within Insurance Companies in Albania - Bazini, Evelina (European Journal of Economics and Business Studies, 2016)
Doing business in today’s competitive environment is becoming very difficult and one of the most important factors for success is considered marketing research. Market research can provide the necessary information about consumer’s needs and expectations which is the first step on new product development and more market it. The aim of this paper is to give an overview of the factors that determine marketing research orientation in insurance companies in Albania, trying to understand of the role that marketing research information plays in anagement.